2013
DOI: 10.1186/1471-2164-14-847
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis of the filamentous fungus Aspergillus nidulans directed to the global identification of promoters

Abstract: BackgroundThe filamentous fungus Aspergillus nidulans has been a tractable model organism for cell biology and genetics for over 60 years. It is among a large number of Aspergilli whose genomes have been sequenced since 2005, including medically and industrially important species. In order to advance our knowledge of its biology and increase its utility as a genetic model by improving gene annotation we sequenced the transcriptome of A. nidulans with a focus on 5′ end analysis.ResultsStrand-specific whole tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
62
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(71 citation statements)
references
References 76 publications
(90 reference statements)
7
62
0
Order By: Relevance
“…This means NATs in A. flavus might regulate gene expression mainly at the post-transcriptional level, which is consistent with the conclusion reported by Donaldson et al [28]. The inside-biased NAT distribution in A. flavus , however, was different from the 3′-biased antisense transcription in A. nidulans [72] and the mammalian NAT distribution, where NATs are usually enriched in the region of the 250 bp upstream sequence and the 1.5 kb downstream sequence [26]. The transcriptional level of A. flavus genes with NATs (average RPKM 253.59) was much higher compared to genes without NATs (average RPKM 54.50; Fig.…”
Section: Resultssupporting
confidence: 91%
“…This means NATs in A. flavus might regulate gene expression mainly at the post-transcriptional level, which is consistent with the conclusion reported by Donaldson et al [28]. The inside-biased NAT distribution in A. flavus , however, was different from the 3′-biased antisense transcription in A. nidulans [72] and the mammalian NAT distribution, where NATs are usually enriched in the region of the 250 bp upstream sequence and the 1.5 kb downstream sequence [26]. The transcriptional level of A. flavus genes with NATs (average RPKM 253.59) was much higher compared to genes without NATs (average RPKM 54.50; Fig.…”
Section: Resultssupporting
confidence: 91%
“…In contrast to our RNA-seq results, the An4394 transcript was not detected in the VG (0 hr) in these experiments. This observation is in agreement with results described by Sibthorp et al (2013) that reported low reads per kilobase per million mapped reads (RPKM) levels for An4394 in either minimal or complete Aspergillus culture medium. Furthermore, we were unable to detect the An4394::GFP chimera in vegetative hyphae either by fluorescence microscopy or by Western blot.…”
Section: Global Analysis Of Flbb Activity In the Regulation Of Genes supporting
confidence: 93%
“…The larger increase for U. maydis was likely due to sequencing RNA from haploids, dikaryons, and teliospores (dormant and germinating) while only RNA from haploids was sequenced for U. hordei and only RNA from haploids and dikaryons for S. reilianum . Increased numbers of detected transcripts were also observed by analyses of deep RNA-seq data of F. graminearum yielding a 1.2-fold increase and that of Aspergillus nidulans yielding a 4.2-fold increase [38, 40]. Among the novel transcripts detected in our study, a small number have putative ORFs.…”
Section: Discussionsupporting
confidence: 74%